HUBUNGAN ANTARA BUDAYA ORGANISASI DENGAN PERILAKU PROSOSIAL PADA MAHASISWA DI YOGYAKARTA - Abd Razik (SINERGI : Jurnal Riset Ilmiah, 2026)
The development of organizations today has certainly expanded significantly, both through prosocial work programs and the culture of internal organizational interaction itself, which is increasingly progressing. This study aims to analyze the relationship between organizational culture and prosocial behavior among university students in Yogyakarta. The research method used in this study was quantitative, employing a correlational approach using the Spearman correlation technique with respondents from college students currently working in organizations in the Yogyakarta area. The results of this study indicate a relationship between prosocial behavior and organizational culture. This is evidenced by the Spearman correlation value (0.347) and a p-value of 0.000, which is categorized as a moderate relationship. These results indicate that a positive and conducive organizational culture will be more effective through a campus environment that supports cooperation and participation and can encourage students to demonstrate prosocial behaviors such as mutual assistance, cooperation, and contribution.